Pengaruh Penggunaan Tepung Tulang Ikan Tuna dan Tepung Eceng Gondok (Eichhornia crassipes) dalam Pakan Buatan Terhadap Pertumbuhan Ikan Nila (Oreochromis niloticus) - Tamar Mustari (FPIK UNIDAYAN, 2022)
The research aims to determine the effect of adding fish bone meal with water hyacinth flour to artificial feed on the growth of tilapia (Oreochromis niloticus). The study was conducted for 60 days, using 9 pieces of happa media with a size of 1 x 1 x 1 m, and put them in a fresh water pond. The test feeds, namely tuna fish bone meal and water hyacinth flour made according to the procedure for making artificial feed, were given 2 times/day as much as 10%/day of the total fish weight. The organism was tilapia (O. niloticus), size 4-7 gram/head. The design used was a completely randomized design 3 treatments and 3 replications. Treatments A (30% water hyacinth meal), B (30% fish bone meal), and C (15% fish bone meal and 15% water hyacinth meal). The results showed that the use of fish bone meal and water hyacinth flour had an effect on the growth of tilapia (O. niloticus) (P<0.05). The highest absolute growth and specific growth were in C treatment (15% fish bone meal and 15% water hyacinth meal) namely 9.27 ± 0.96 grams and 1.74 ± 0.25%/day with the best feed conversion of 4.55 ±0.43. The lowest results were obtained in A treatment (0% fish bone meal), namely 6.37 ± 0.95 grams and 1.48 ± 0.39 %/day with feed conversion of 5.21 ± 1.41, while the survival rate during the study is 100% with proper water quality for the growth and survival rate of tilapia.